Applied Physics, System Science and Computers III : Proceedings of the 3rd International Conference on Applied Physics, System Science and Computers (APSAC2018), September 26-28, 2018, Dubrovnik, Croatia /: Proceedings of the 3rd International Conference on Applied Physics, System Science and Computers (APSAC2018), September 26-28, 2018, Dubrovnik, Croatia. ([2019]) - Unknown
No abstract available